2017
DOI: 10.1177/2309499017731626
|View full text |Cite
|
Sign up to set email alerts
|

The optimal protocol to reduce blood loss and blood transfusion after unilateral total knee replacement: Low-dose IA-TXA plus 30-min drain clamping versus drainage clamping for the first 3 h without IA-TXA

Abstract: The drainage clamping method can be safer than IA-TXA administration in patients with risk factor of venous thromboembolic complication. Furthermore, the IA-TXA administration can be more optimal than drainage clamping in patients with high bleeding tendency or lateral retinacular release during TKR, who would be concerned about postoperative wound complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Raleigh et al concluded that clamping drains intermittently resulted in significantly less postoperative drainage than that observed with continuous suction drainage [37]. Park et al found that intraarticular tranexamic acid administration plus 30-min drain clamping also significantly reduced postoperative drainage [38].…”
Section: Discussionmentioning
confidence: 99%
“…Raleigh et al concluded that clamping drains intermittently resulted in significantly less postoperative drainage than that observed with continuous suction drainage [37]. Park et al found that intraarticular tranexamic acid administration plus 30-min drain clamping also significantly reduced postoperative drainage [38].…”
Section: Discussionmentioning
confidence: 99%
“…Different measures to reduce operative blood loss have been employed in orthopedic surgery to reduce the need for transfusion and hasten the patient's recovery in the post-operative period [2]. A frequently employed such technique is transfusion of autologous blood which also reduces the risk of infection, but it is expensive and not every center has the facility [2,3]. Another method for control of the perioperative blood loss is the application of anti-fibrinolytic agents including aprotinin, epsilon-aminocaproic acid, and tranexamic acid (TXA) [4].…”
Section: Discussionmentioning
confidence: 99%
“…During TKA, Patient's recovery may be affected negatively by blood loss. Allogenic blood transfusion may be needed on the basis of amount of blood lost during the procedure [2]. Moreover, high post-operative infections are also associated with this procedure [3], measures which can reduce operative loss of blood and subsequent necessitating blood transfusion have always been adored and a hot focus of medical research [2].…”
Section: Introductionmentioning
confidence: 99%
“…Different measures are used to reduce intra operative blood loss have been employed in orthopedic surgery to reduce the need for transfusion and hasten the patient's recovery in the post-operative period [9]. One technique is transfusion of autologous blood which also reduces the risk of infection and risk of transfusion reaction but it is expensive and not every center has facility for this [9,10]. Another technique to reduce perioperative blood loss is the application of antifibrinolytic agents including aprotinin, epsilonaminocaproic acid, and tranexamic acid (TXA).…”
Section: Discussionmentioning
confidence: 99%